Copper-catalyzed (4+1) and (3+2) cyclizations of iodonium ylides with alkynes. Issue 77 (26th August 2020) - Liang, Hao; He, Xiaobo; Zhang, Yaqi; Chen, Bin; Ouyang, Jia-sheng; Li, Yongsu; Pan, Bendu; Subba Reddy, Chitreddy V.; Chan, Wesley Ting Kwok; Qiu, Liqin
Abstract : The copper(ii )-catalyzed (4+1) cyclizations and copper(i )-catalyzed (3+2) cycloadditions of iodonium ylides and alkynes have been successfully developed. The corresponding highly functionalized heterocyclic products were prepared conveniently. Abstract : The copper(ii )-catalyzed (4+1) cyclizations and copper(i )-catalyzed (3+2) cycloadditions of iodonium ylides and alkynes were successfully developed by employing efficient and safe iodonium ylides instead of traditional diazo compounds. Highly functionalized dimethyl ( E )-3-benzylideneindoline-2, 2-dicarboxylates and methyl 5-(2-hydroxyphenyl)-2-methoxy-4-phenylfuran-3-carboxylates were conveniently prepared in moderate to excellent yields. The possible reaction mechanisms were also discussed.